THE EFFECT OF THE EXTERNAL AUDITOR'S USE OF MODERN TECHNOLOGIES ON THE STAKEHOLDERS’ DECISIONS - Faez Abdulhasan Jasim Allami; Sadeq Hussein Nabhan; Dr Ali Khazaal Jabbar (Scholar Express Journals, 2022)
The goal of the study is to show how important it is for external auditors to use modern technologies in the audit process in order to keep up with modern scientific developments in various fields, as well as their reliance on advanced and modern applications, methods, and technologies that can help reduce human errors, costs, and effort. The study also investigates if it can play a significant role in detecting mistakes, fraud, and other fraudulent practices that are difficult to detect using standard auditing methods in many circumstances, especially given the development and diversity of fraud ways. The relevance of the external auditor employing contemporary technology on the opinion that he presents, especially if we know that there will be numerous parties who will be reflected in this opinion and who will be called (stakeholders). They are the beneficiaries of the opinion of the external auditor in making various decisions, and to whom the external auditor will be legally responsible .
Keywords: auditor; technologies; process; external